Transanal endoscopic microsurgery for rectal adenomas: single center experience - Narimantas Evaldas Samalavicius; Edgaras Smolskas; Kipras Mikelis; Robertas Samalavicius (Videosurgery and Other Miniinvasive Techniques)
Introduction: Transanal endoscopic microsurgery (TEM) is a method of choice for the local treatment of rectal adenomas. Though generally considered as a safe method, some authors have expressed skepticism about the anorectal function following TEM. Aim: To review our experience in using TEM for removal of rectal adenomas. We focused on morbidity, local recurrence rates, and anorectal function following the operation. Material and methods : The study included 72 patients who underwent TEM for rectal adenomas from December 2009 to November 2014 at the Department of Surgical Oncology, National Cancer Institute. Of the 72 patients, 31 (43.1%) were lost in the follow-up. We recorded the demographics, operative details, final pathology, post-operative length of stay, post-operative complications, recurrences and functional outcome for each of the 41 (56.9%) remaining participants. Results : Of the 41 eligible patients, 19 (46.3%) were male and 22 (53.7%) were female. The mean age of our patients was 66.8 years. There were no intraoperative complications. In 4 (9.8%) cases, postoperative complications were observed – urinary retention (2 cases, 4.9%) and postoperative hemorrhage (2 cases, 4.9%). All complications were treated conservatively. There was a single case (2.4%) of adenoma recurrence during the follow-up period. The mean score of the FISI questionnaire was 7.6 ±9.2 (ranging from 0 to 36), and the mean Wexner score was 2.3 ±3.4 (ranging from 0 to 17). Conclusions : Transanal endoscopic microsurgery in our experience demonstrated low complication and recurrence rates, and good functional results. We conclude that TEM is an effective and safe method for the treatment of rectal adenomas.